2023
DOI: 10.3390/lubricants11020086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu-Doped Carbon Quantum Dot Dispersion Liquid on the Lubrication Performance of Polyethylene Glycol

Abstract: Energy saving and reduced consumption of key materials such as bearings in high-end equipment can be realized by synthesizing a new lubricating functional additive, copper-doped carbon quantum dot dispersion liquid (Cu-CQDs) via hydrothermal reaction with glycerol, cupric chloride dihydrate, and choline chloride as raw materials. The influence of the dispersion liquid containing Cu-CQDs nanoparticles on the lubricating properties of polyethylene glycol (PEG200) was investigated on a four-ball friction tester. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…To improve energy efficiency and reduce resource consumption of bearings and other critical materials in high-end equipment, many scientists have used "copper" as a raw material for synthetic modification of other lubricating materials. Liu et al [178] successfully synthesized a new type of copper-carbon quantum dot dispersions (Cu-CQDs) (Figure 8) with a lubricating function by hydrothermal reaction using glycerol, choline chloride, and copper chloride dihydrate as raw materials. They tested the effect of dispersions containing Cu-CQDs nanoparticles on the lubrication properties of polyethylene glycol (PEG200) bearing materials by testing them on a four-ball friction tester, which concluded that the synthesized Cu-CQDs have an average particle size of about 8.33 nm and that their application in dispersions significantly enhanced the lubrication properties of PEG.…”
Section: Analysis Of Wind Power Bearing Lubrication Research Based On...mentioning
confidence: 99%
“…To improve energy efficiency and reduce resource consumption of bearings and other critical materials in high-end equipment, many scientists have used "copper" as a raw material for synthetic modification of other lubricating materials. Liu et al [178] successfully synthesized a new type of copper-carbon quantum dot dispersions (Cu-CQDs) (Figure 8) with a lubricating function by hydrothermal reaction using glycerol, choline chloride, and copper chloride dihydrate as raw materials. They tested the effect of dispersions containing Cu-CQDs nanoparticles on the lubrication properties of polyethylene glycol (PEG200) bearing materials by testing them on a four-ball friction tester, which concluded that the synthesized Cu-CQDs have an average particle size of about 8.33 nm and that their application in dispersions significantly enhanced the lubrication properties of PEG.…”
Section: Analysis Of Wind Power Bearing Lubrication Research Based On...mentioning
confidence: 99%
“…The element of the transition layer of the Ti−coated diamond and the copper element continuously infiltrated each other during cyclic wear, as shown in Figure 14. Under the hindrance of the diamond, the copper chips were observed to be ground into nano−scale, which helped to improve the wear resistance of the composite coating [32]. The transition layer on the surface of the diamond was worn, but the diamond was still tightly embedded in the matrix and tightly bonded.…”
Section: Wear-resistant Propertymentioning
confidence: 99%